Clinical usefulness of prethymectomy plasmapheresis in patients with myasthenia gravis: A systematic review and meta-analysis - Reis, Tarcisio A. [UNESP]; Cataneo, Daniele C. [UNESP]; Cataneo, Antônio Jose Maria [UNESP] (Oxford University Press (OUP), 2019)
OBJECTIVES: Our goal was to evaluate, through a systematic review, the efficacy of plasmapheresis in the preoperative preparation of the patient for a thymectomy for the treatment of myasthenia gravis. METHODS: MEDLINE, Embase, LILACS, Scopus and CENTRAL databases were searched. The following outcomes were evaluated: myasthenic crisis, mortality, pneumonia, bleeding, use of mechanical ventilation, length of hospital stay and intensive care unit (ICU) stay. RevMan 5.3 software provided by the Cochrane Collaboration was used for the meta-analysis. RESULTS: The total number of patients evaluated in the 7 included studies was 360. Plasmapheresis during the preoperative period did not decrease the myasthenic crisis [risk ratio (RR) 0.36, 95% confidence interval (CI) 0.08-1.66; I2 = 44%; 5 studies, 243 patients]. There was also no change in the mortality rate (RR 0.7, 95% CI 0.11-4.62; I2 = 0%; 3 studies, 172 patients) or pneumonia cases (RR 0.28, 95% CI 0.07-1.09; I2 = 27%; 5 studies, 272 patients). Bleeding was greater in patients who underwent plasmapheresis (mean difference 34.34 ml; 95% CI 24.93-43.75; I2 = 0%). We evaluated the following outcomes: need for mechanical ventilation, hospital stay, ICU stay and mechanical ventilation, but these outcomes were not adequate to perform the meta-analysis due to the high heterogeneity among the studies. Subgroup analysis showed that plasmapheresis performed during the preoperative period in patients with severe disease (Osserman III and IV) decreased the myasthenic crisis postoperatively (RR 0.12, 95% CI 0.02-0.65; I2 = 63%). CONCLUSIONS: Plasmapheresis may reduce the myasthenic crisis during the postoperative period in patients with severe disease but may produce little or no difference in patients with mild clinical expression of the disease.
Keywords: Myasthenia gravis; Plasmapheresis; Systematic review; Thymectomy